Analisis Rasio Likuiditas, Solvabilitas, Dan Profitabilitas Terhadap Kinerja Perusahaan Dengan Manajemen Laba Sebagai Variabel Intervening - Dhea Putri Novitasari; Faizal Satria Desitama (Journal Of Business, Finance, and Economics (JBFE), 2023)
This study aims to analyze the effect of liquidity, solvency and profitability ratios on financial performance with earnings management as an intervening variable. This study uses a quantitative approach. The data collection method uses secondary data in the form of financial reports of food and beverage companies listed on the IDX 2018-2021. The sampling technique used in this study used purposive sampling. The data analysis technique used in this study is cross section data regression method with multiple regression analysis. The results showed that the liquidity ratio (current ratio) has a significant effect on earnings management and does not have a significant effect on company performance. The solvency ratio (debt to equity ratio) has no significant effect on earnings management and has a significant effect on company performance. Profitability ratios (net profit margin) have a significant effect on earnings management and company performance. Earnings management has a significant effect on company performance in food and beverage sub-sector manufacturing companies listed on the IDX for the 2018-2021 period.